Emergency arterio-venous loop for free-flap defect reconstruction of the lower thigh with a post-irradiated and heavily infected wound - Taeger, Christian; Arkudas, Andreas; Beier, Justus; Horch, Raymund E. (International Wound Journal, 2015)
Although being a safe and standardised procedure, free-flap reconstruction can be harmful if unpredictable situations occur intraoperatively. The case presented reveals a situation in which an unscheduled interdisciplinary approach allowed to complete our reconstructive aim. An extensive defect at the thigh was planned for reconstruction by means of a free rectus abdominis flap. As the distant part of the flap showed a compromised perfusion during operation and had to be partially discarded, our colleagues from the vascular surgery department created an arterio-venous loop for anastomosis. This allowed a more distant positioning of the flap and ensured a complete defect reconstruction.
EVALuna2:15569